GENDER ANALYSIS ON EDUCATION AND INCOME: A PARADIGM SHIFT AMONG RURAL PARENTS WITH CHILDREN IN REGGIO EMILIA EARLY CHILDHOOD DEVELOPMENT IN NORTHERN NIGERIA (FUDMA JOURNAL OF SCIENCES, 2023)
There is global progress toward gender equality with 68% of the countries in the World Economic Forum Gender Gap Report of 2019. Despite the progress, education and income are among areas in which gender is still not equally enabled in developing regions. As the world is progressing in reaching gender-equal access to education and income some programs appeared in gender equity to wipe out some obstacles faced by girls and women in education and income which may invariably improve the socio-economic status. The quantitative- exploratory-Correlational design was used in a gender-disaggregated form on the parents with children in the Reggio Emilia Early Childhood Development (REA-ECD) centres. The sample size of 405 with 204 females and 201 males was used through multistage-systematic random sampling. The instrument for data collection was adapted, data collection with the aids of trained enumerators and analysed in descriptive and binary logistic regression. The results show a significant improve (44.9%) with tertiary education, mean income N34,572. 840, [USD138.291]and 28.5 times (odds=29.46) more likelihood of high REA-ECD acceptance for girls and boys to attend schools. These revealed the need for more programs involving more women as well as laws and policies that enable girls and young women to attend school. More studies in future especially longitudinal to ascertain any dynamism in development over time.  Hence, in developing countries, there are still barriers limiting women and girls opportunity.
Keywords: Gender; Reggio Emilia Early Childhood Development; Northern Nigeria